THE FUTURE OF ISLAMIC FINANCIAL LITERACY: EMPOWERING MILLENNIALS AND GEN Z WITH SHARIAH-COMPLIANT KNOWLEDGE: MASA DEPAN LITERASI KEUANGAN ISLAM: MEMBERDAYAKAN GENERASI MILENIAL DAN GENERASI Z DENGAN PENGETAHUAN YANG SESUAI DENGAN SYARIAH - Izzatul Munawwaroh (Universitas Wahid Hasyim Semarang, 2024)
The conclusion of this study confirms that Islamic financial literacy among Millennials and Gen Z in Indonesia still needs to be higher. This study aims to explore the importance of Islamic financial literacy for millennials and Gen Z in Indonesia and the role of digital technology in improving their understanding of Islamic finance. Using a qualitative approach and case study in madrasahs, data were obtained through interviews, observations, and documentation. The study results indicate that although the younger generation is very active in using technology, their level of Islamic financial literacy still needs to be higher. This is due to the need for more integration of Islamic financial materials in the formal education curriculum, limited teacher training, and lack of institutional support. In addition, the findings also reveal that digital platforms, such as mobile applications and educational websites, have great potential to deliver more interesting and easy-to-understand information for the younger generation. This study implies the need for curriculum updates and increased training for teachers, as well as cooperation between educational institutions and Islamic financial institutions to improve Islamic financial literacy among students. The implications of these findings are crucial for a more holistic Islamic financial education policy in Indonesia. Improving Islamic financial literacy can create a more financially independent young generation while encouraging the application of Islamic economic principles in everyday life. The contribution of this research lies in the importance of developing a more inclusive curriculum, preparing educators with special training, and encouraging collaboration between educational institutions and Islamic financial institutions to provide materials appropriate to the needs of the millennial and Gen Z generations. Keywords: Islamic Financial Literacy, Millennial Generation, Gen Z, Islamic Financial Education, Education Curriculum.